2010
DOI: 10.1111/j.1439-0485.2009.00337.x
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal fish utilization of a subtropical mangrove‐seagrass ecotone

Abstract: Whereas diel fish migration between mangrove and seagrass habitats has been recognized for decades, quantitative studies have focused mainly on diurnal patterns of fish distribution and abundance. In general, previous studies have shown that fish abundances decline with increasing distance from mangroves; however, evidence for such a pattern at night, when many fishes are actively feeding, is scarce. The present study is the first to report nocturnal fish abundances along a continuous distance gradient from ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 41 publications
2
17
0
1
Order By: Relevance
“…Across transects, seagrass and macroalgae bottom cover was high (range: 66 to 96%) and depths were consistently shallow (range: 72 to 120 cm) out to 120 m from shore (Table 1). Seine net sampling also indicated that the composition and structure of fish communities were very similar among transects (Hammerschlag & Serafy 2010). Consistency in the above physical and abiotic characteristics among transects (Table 1) allowed us to minimize variation in environmental factors which could confound predator-prey relationships (e.g.…”
Section: Methodsmentioning
confidence: 92%
See 2 more Smart Citations
“…Across transects, seagrass and macroalgae bottom cover was high (range: 66 to 96%) and depths were consistently shallow (range: 72 to 120 cm) out to 120 m from shore (Table 1). Seine net sampling also indicated that the composition and structure of fish communities were very similar among transects (Hammerschlag & Serafy 2010). Consistency in the above physical and abiotic characteristics among transects (Table 1) allowed us to minimize variation in environmental factors which could confound predator-prey relationships (e.g.…”
Section: Methodsmentioning
confidence: 92%
“…However, at night, many of these fishes disperse into adjacent seagrass beds to feed. This is supported by a variety of evidence including results from a combination of gut content analysis (Randall 1967), stable isotopes (Kieckbusch et al 2004, Nagelkerken & van der Velde 2004a, visual surveys (Rooker & Dennis 1991, Serafy et al 2003, seine sampling (Hammerschlag & Serafy 2010) and tagging investigations (Verweij & Nagelkerken 2007, Luo et al 2009). Nocturnal selection of seagrass beds by fishes as primary feeding sites appears to be related to elevated availability and accessibility of prey, many of which emerge from the vegetated substrate at night (Mattila et al 1999, Nagelkerken et al 2000, Unsworth et al 2007, Valentine et al 2007).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Por otra parte, la variabilidad ambiental nictimeral es una fuerza acoplada a los ritmos circadianos de los organismos que modifica la estructura comunitaria tanto en abundancia como en diversidad, específica-mente por aspectos de alimentación (Gray et al, 1998;Castillo-Rivera et al, 2005;Oliveira-Neto et al, 2008;Hammerschlag & Serafy, 2010).…”
Section: Introductionunclassified
“…Short-term (e.g., diel or tidal) and long-term (e.g., seasonal or ontogenetic) migrations also commonly occur between adjacent coastal wetlands (e.g., mangroves and coral reefs), with nekton providing a source of connectivity and the transfer of production among otherwise isolated environments comprising more sessile species (e.g., Kneib 1997Kneib , 2000Deegan et al 2000;Ellis and Bell 2008;Hammerschlag and Serafy 2009;Jones et al 2010).…”
Section: Introduction To Aquatic Fauna Of Vegetated Marine Habitatsmentioning
confidence: 99%